Volatilome Metabolomics and Databases, Recent Advances and Needs - Cumeras, Raquel (Current Metabolomics, 2017)
Background: Metabolomics is leaving a gold era, and volatilomics is finding its niche due to its non-invasiveness. Volatilomics is the totality of Volatile Organic Compounds (VOCs) produced by all living organisms (plants, animals, etc.), the analyses of those volatiles can offer, amongst others, the possibility of rapid diagnoses of patients using non-invasive techniques. However, the lack of a central core database of volatilome is a drawback when identifying the biological output of experimental identified metabolites. Objective: Give an accurate state-of-the-art insight of volatilomics, by revising the published reviews since 2014, giving an accurate list of studied diseases within volatilomics and finally, a detailed list of available VOC databases. Methods: Recent progress in the volatile metabolomics development, applications and databases are reviewed Results: What are VOC’s, depending on their context or sector. Volatilome is extensively explained and analyzed the VOC etiology (endogenous/exogenous), with special interest in the human volatilome. The amount of review articles (48) published since 2014 indicates that volatilomic is on its height (or ascending) momentum. Biofluid sources and diseases studied are reviewed. Also, we mention what are the current trends of volatilomics in systems biology and precision medicine. Finally, the steps involved in the data analysis and the available volatilome databases are resumed. Conclusion: The advances in volatile metabolomics are increasing, and a broad spectrum of human diseases or disorders are being interrogated, so the need of detailed databases list of both healthy and disease metabolites is increasing.
Keywords: healthy